2010
DOI: 10.1007/s10482-010-9413-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with the rhizosphere of pioneer plants (Bahia xylopoda and Viguiera linearis) growing on heavy metals-contaminated soils

Abstract: In this study, the bacterial communities associated with the rhizospheres of pioneer plants Bahia xylopoda and Viguiera linearis were explored. These plants grow on silver mine tailings with high concentration of heavy metals in Zacatecas, Mexico. Metagenomic DNAs from rhizosphere and bulk soil were extracted to perform a denaturing gradient gel electrophoresis analysis (DGGE) and to construct 16S rRNA gene libraries. A moderate bacterial diversity and twelve major phylogenetic groups including Proteobacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Two phylotypes (RS23, RS17) were related to Salinimicrobium catena isolated from sediments of oil fields in the South China Sea [29] within Flavobacteriaceae. The Acidobacteria group was dominant in the AS clone library and the sequences were related (88-99%) to uncultured Solibacter isolated from hydrocarbon contaminated soils [30], and uncultured Acidobacteria isolated from the heavy metal contaminated soils [31]. No phylotype from SS2 was found related to this group.…”
Section: Resultsmentioning
confidence: 99%
“…Two phylotypes (RS23, RS17) were related to Salinimicrobium catena isolated from sediments of oil fields in the South China Sea [29] within Flavobacteriaceae. The Acidobacteria group was dominant in the AS clone library and the sequences were related (88-99%) to uncultured Solibacter isolated from hydrocarbon contaminated soils [30], and uncultured Acidobacteria isolated from the heavy metal contaminated soils [31]. No phylotype from SS2 was found related to this group.…”
Section: Resultsmentioning
confidence: 99%
“…This microbial biodiversity reflects the relatively aerobic nature below the bagasse pile surface under the collection conditions. Comparative analysis based on 16S rDNA sequences revealed that the bacterial community in the bagasse pile was mostly related to the bacteria in the soil and compost (EU676446, GQ360076), 23) especially from high-temperature sites (AM749771, GU113028), 24) A substantial number of the sequences were also related to the microbial assemblage in geothermal ecosystems e.g., hot spring, 11) and the thermophilic cyanobacterial mat (EF032761) as well as in waste water sludge (FJ536903). 25) Although the analysis might have been biased due to the availability of sequences from different environments in the existing databases, this suggests significant similarities and differences between the microbial groups in bagasse piles and other ecosystems.…”
Section: Prokaryotic Microbial Diversitymentioning
confidence: 99%
“…The denaturing gradient gel electrophoresis (DGGE) analysis was conducted according to the methods described by Nakatsu et al (2000) and Navarro-Noya et al (2010). The DGGE gels were analyzed with the Quantity One software (Bio-Rad).…”
Section: Biological Characteristics Of Compost Extractsmentioning
confidence: 99%